Two new species of the genus Notacanthurus from China (Ephemeroptera: Heptageniidae, Ecdyonurinae) - Zhang, Wei; Zhang, Min; Han, Na; Zhou, Chang-Fa (Zootaxa, 2020)
Previously, only three of seven species in the Asian genus Notacanthurus were reported both nymphs and imagoes, and no Chinese species was found. Here two new species collected from China, which are named as Notacanthurus maculatus sp. n. and N. lamellosus sp. n. respectively, are described and pictured in detail. The nymph of N. maculatus sp. n. has following combined characters: posterior margin of sternum IX straight, claws with two subapical denticles, and gills V–VI with arrow-like accessory lobes. The male imago has unspecialized anterior margin of head and Electrogena-like penis lobes. The second species N. lamellosus sp. n. is more distinguishable. Its nymph has pale dots on head, median dorsal ridges on abdominal terga I–IX, claws with five subapical denticles, and dorsal lamellae of gills II–IV divided into two portions. Anterior margin of male imago is not protruding either, forewings have less pigmented crossveins between Sc and R1, and penis lobes have apical and ventral sclerites. A key to all known nymphs of the genus is provided.